Exploring Low Levels of Inter-Parental Agreement Over South African Fathers' Parenting Practices. Issue 1 (March 2018) - Mercer, Gareth D.; Jewkes, Rachel; Esser, Monika; MacNab, Ying C.; Patrick, David M.; Buxton, Jane A.; Bettinger, Julie A.
High rates of residential separation of fathers and children in South Africa demand reliable methods of collecting data on the parenting practices of nonresident fathers. Using questionnaire data from matched mother–father pairs, we assessed the reliability of mother's reports of father's involvement in infant care as a proxy for father's own reports. Agreement between parental reports was reasonable for father's financial provisioning and time spent with the infant, but poor for father's engagement in direct caregiving, decision-making responsibility, and assistance with household chores. Across a range of activities, fathers reported higher levels of involvement than were acknowledged by mothers. Disagreement over definitions of the underlying parenting practices being assessed and definitions of the response categories on the questionnaire appeared to contribute to low levels of overall agreement. Mother and father reports should not be treated interchangeably in research on father involvement. Ideally, future research will incorporate data from multiple observers.